Mechanisms of steroidal implants to improve beef cattle growth: a review. Issue 1 (1st January 2020) - Smith, Zachary K.; Johnson, Bradley J.
ABSTRACT: For more than 60 y, beef cattle producers have safely used various types of growth-enhancing technology (GET ) such as steroidal implants with anabolic activity and orally active beta-adrenergic agonists to increase skeletal muscle growth rate, improve carcass leanness, increase average daily gain (ADG ), and alter dry matter intake (DMI ) compared to non-treated cattle. Generally, the use of a GET increases ADG and only moderately affects DMI relative to non-treated cattle; subsequently, this enhances the rate of live weight gain relative to the amount of feed needed to achieve that gain, this is referred to as feed efficiency (G:F ). When a producer chooses to utilize a GET, improvements in treated cattle over non-treated cattle are typically in the range of 8% to 28% for ADG and 5% to 20% for G:F. This review of the literature is intended to provide up to date insight into the mechanisms of how steroidal implants with anabolic activity enhance cattle growth and how these technologies have evolved since their introduction to U.S. beef producers nearly 60 y ago.